Implementation of Supervision of Over Dimension Over Load Violations in Kulon Progo Regency - Vicki Dwi Purnomo; Kelik Endro Suryono (PT FORMOSA CENDEKIA GLOBAL, 2022)
Transportation or communication problems are problems that are always faced by developing countries as well as developed countries. And one of the problems currently experienced in Indonesia is the violation of Over Dimension and Over Loading. This study aims to determine the implementation of supervision and the efforts made by the Kulon Progo Regency Transportation Service in supervising vehicles that are Over Dimension Over Loading. The type of research conducted was qualitative research using interview, observation and questionnaire methods. The results of the study showed that the supervision was carried out by using indicators. Setting standard measuring instruments to obtain results with indicators of being maintained. Performing assessment or evaluation actions with the data obtained that 50% of respondents stated that they were in the maintained category. and take corrective action. Efforts made by the Kulon Progo Regency Transportation Service in dealing with Over Dimension Over Loading vehicles are: Implementation of regulations, Increasing the implementation of supervision, Improving UPPKB Infrastructure, Collaborating with various parties (Police, Denpom, DIY Provincial Transportation Agency and Satpol PP